The Relationships Among Pain, Depression, and Physical Activity in Patients With Heart Failure. Issue 5 (September 2017) - Haedtke, Christine; Smith, Marianne; VanBuren, John; Klein, Dawn; Turvey, Carolyn
Abstract : Introduction: Increasing patients' physical activity levels holds many opportunities to facilitate health and well-being among those with heart failure (HF) by improving HF symptoms and decreasing depression and pain. Given low exercise participation rates, an essential first step to increase exercise rates is to evaluate how pain and depression may further influence engagement in exercise programs. Aims: The aims of this study were to describe the level of physical activity and exercise that patients with HF with depression achieve and to investigate the relationships among pain, depression, total activity time, and sitting time. Methods: In this correlational cross-sectional study, we analyzed data from 61 participants with depression and New York Heart Association class II to IV HF. Results and Conclusions: The total time spent being active was less than 1 hour per day. Depressed patients with HF have much lower physical activity levels than the general public. Decreasing sitting time and increasing light activity levels hold promise to improve pain and depression symptoms.